2007
DOI: 10.1016/j.rmed.2007.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoalveolar matrix metalloproteinase 9 relates to restrictive lung function impairment in systemic sclerosis

Abstract: Systemic sclerosis (SSc) is frequently associated with interstitial lung disease (ILD) often leading to lung fibrosis. In this study we investigated whether matrix metalloproteinase 9 (MMP-9) and its natural inhibitor; the tissue inhibitor of matrix metalloproteinase 1 (TIMP-1), would be associated with remodelling in ILD in SSc. Levels of total MMP-9, pro-MMP-9 and TIMP-1 were measured in bronchoalveolar lavage (BAL) fluid from nine SSc patients with ILD, seven SSc patients without ILD and 16 age- and sex-mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 42 publications
3
25
0
Order By: Relevance
“…It is likely that abnormalities of the fibrotic lung will be reflected in the composition of the BALF, and numerous investigators have examined the cellular and soluble components of BALF in both SSc-associated and idiopathic ILDs. In keeping with prior reports that MMP-9 is elevated in the idiopathic forms of UIP and NSIP [17], Anderson et al [18] demonstrated increased total and pro-matrix metalloproteinase-9 (MMP-9) levels in the BAL fluid of individuals with SSc-ILD versus individuals with SSc and no evidence of ILD and normal controls. BALF levels of TIMP-1, however, were elevated in all individuals with SSc, regardless of the presence of ILD [18].…”
Section: Extracellular Matrix Homeostasissupporting
confidence: 66%
See 1 more Smart Citation
“…It is likely that abnormalities of the fibrotic lung will be reflected in the composition of the BALF, and numerous investigators have examined the cellular and soluble components of BALF in both SSc-associated and idiopathic ILDs. In keeping with prior reports that MMP-9 is elevated in the idiopathic forms of UIP and NSIP [17], Anderson et al [18] demonstrated increased total and pro-matrix metalloproteinase-9 (MMP-9) levels in the BAL fluid of individuals with SSc-ILD versus individuals with SSc and no evidence of ILD and normal controls. BALF levels of TIMP-1, however, were elevated in all individuals with SSc, regardless of the presence of ILD [18].…”
Section: Extracellular Matrix Homeostasissupporting
confidence: 66%
“…In keeping with prior reports that MMP-9 is elevated in the idiopathic forms of UIP and NSIP [17], Anderson et al [18] demonstrated increased total and pro-matrix metalloproteinase-9 (MMP-9) levels in the BAL fluid of individuals with SSc-ILD versus individuals with SSc and no evidence of ILD and normal controls. BALF levels of TIMP-1, however, were elevated in all individuals with SSc, regardless of the presence of ILD [18]. It is possible that the balance between key MMPs and TIMPs in the alveolar compartment may serve as a stronger predictor of the presence or severity of ILD, and further study is warranted.…”
Section: Extracellular Matrix Homeostasissupporting
confidence: 66%
“…Biomarkers of various kinds have an important theoretical role in this regard, both in initial evaluation and in monitoring. However, candidate serum, bronchoalveolar lavage and imaging biomarkers in CTD-ILD have mostly been studied only at a single point in time [34], including surfactant protein A and B (SP-A, SP-B) [35,36,37], Krebs von den Lungen (KL)-6 [35,38,39,40,41], other lung epithelium-derived proteins, as well as chemokines, cytokines, matrix metalloproteinases and interleukins [34,42,43,44,45,46,47,48]. Serial biomarker trends have the potential to refine prognostic evaluation with exciting possibilities with the introduction of a therapy, and short-term biomarker changes might provide invaluable information on longer-term efficacy.…”
Section: Pulmonary ‘Disease Activity' In Monitoringmentioning
confidence: 99%
“…MMP-9 (gelatinase B), associated with chronic inflammatory autoimmune diseases and conditions characterised by excessive fibrosis, was significantly increased in serum of SSc patients compared to healthy controls [81] and in bronchoalveolar lavage of SSc-ILD patients [82]. Interestingly, circulating levels of MMP-12 have been reported to be tightly inversely correlated with FVC ( r = −0.82), and MMP-12 staining to be significantly increased in SSc-ILD lungs compared to normal controls [83].…”
Section: Matrix Metalloproteinases/tissue Inhibitors Of Metallopromentioning
confidence: 99%